Polymer, preparation method, dispersing agent, positive electrode slurry, positive electrode plate, secondary battery and electric device
By developing a polymer dispersant containing end groups such as carboxy group and ester group, the dispersion problem of the positive electrode active substance slurry system with different degrees of graphitization is solved, the battery performance and production efficiency are improved, and the cost is reduced.
Patent Information
- Application Number
- CN202310866463.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-07-14
AI Technical Summary
In the prior art, dispersants cannot be suitable for slurry systems of positive electrode active substances with different degrees of graphitization, resulting in poor battery performance, high manufacturing cost and low production efficiency.
Develop a polymer dispersant containing end groups and non-polar groups of carboxyl, ester, sulfonic acid, sulfonate or phosphate ester group, prepared by polycondensation and end-malization reaction, with a wide range of universal It has a high dispersion ability and is suitable for cathode active substances with different degrees of graphitization.
It improves the solid content of the slurry, slows down the gel phenomenon, reduces the diaphragm resistance of the electrode sheet, improves the flexibility of the electrode sheet, improves the first-time Coulomb efficiency and high-temperature cycling performance of the battery, and reduces manufacturing and production costs.
Smart Images

Figure CN119306942A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a polymer, a preparation method, a dispersant, a positive electrode slurry, a positive electrode sheet, a secondary battery and an electrical device. Background Art
[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.
[0003] As the main component of the secondary battery, the positive electrode sheet directly affects the application performance of the secondary battery. The positive electrode sheet is generally composed of a current collector, a positive active material, a conductive agent, and a binder. However, the positive active material is generally a nano-scale material, which has a large specific surface area, resulting in a higher surface activity. During the homogenization of the positive electrode slurry, agglomeration is very likely to occur, forming larger agglomerates, which affects the coating effect of the electrode, resulting in low conductivity of the prepared electrode sheet, which directly affects the electrochemical performance of the battery. In the prior art, a dispersant is generally added to improve the dispersibility of the slurry. However, the dispersant in the prior art cannot be applied to a slurry system containing positive active materials with different degrees of graphitization produced by different processes. The dispersant in the prior art has poor versatility, which is not conducive to reducing manufacturing costs. Therefore, it is necessary to develop a new dispersant to be applicable to a slurry system containing positive active materials produced by different processes. Summary of the invention
[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a polymer, which is used as a dispersant to adapt to positive electrode active materials with different degrees of graphitization, and can improve the dispersibility of the slurry system containing positive electrode active materials with different degrees of graphitization, and can effectively increase the solid content of the slurry, slow down the gelation phenomenon of the slurry, reduce the diaphragm resistance of the electrode, improve the flexibility of the electrode, and improve the first coulombic efficiency and high-temperature cycle performance of the battery.
[0005] The first aspect of the present application provides a polymer, the polymer comprising a structure shown in Formula I,
[0006] X′-LX Formula Ⅰ
[0007] wherein X comprises at least one of a carboxyl group, an ester group, a sulfonic acid group, a sulfonate group, a phosphoric acid group, and a phosphoric acid ester group;
[0008] X' comprises a nonpolar group;
[0009] L comprises structural units represented by formula II and formula III,
[0010]
[0011] R 1 Contains C 1-12 Alkylene, C 6-12 Aromatic group, At least one of R 2 Contains C 1-12 Alkylene, C 6-12 Aromatic group, At least one of R 3 Contains C 1-12 Alkylene, C 6-12 Aromatic group, At least one of R 4 Contains C 1-12 Alkylene, C 6-12 Aromatic group, At least one of R 5 Contains hydrogen or C 1-3 alkyl,
[0012] EO represents -CH 2 -CH 2 -O-, PO represents -CH(CH 3 )-CH 2 -O-, m1, m2, m3, m4 are each independently an integer between 1 and 10, and n1, n2, n3, n4 are each independently an integer between 0 and 10.
[0013] The end group of one end of the polymer contains a non-polar group, which is lipophilic, and the end group of the other end contains at least one of carboxyl, ester, sulfonic acid, sulfonate, phosphoric acid, and phosphate, which is a polar group and is hydrophilic. When the polymer is added to the slurry system, the carboxyl, ester, sulfonic acid, sulfonate, phosphoric acid, or phosphate at one end is adsorbed on the surface of the solid particles as an anchor point, and the non-polar group at the other end is suspended in the slurry to form a steric barrier. When the solid particles approach each other, this steric barrier will produce a strong repulsive force, preventing the particles from agglomerating, and forming a uniformly dispersed and stable slurry. At the same time, the structural units shown in Formula II and Formula III contain ester groups and amide groups, both of which are polar groups, which can produce strong intermolecular induction forces and further improve the dispersing effect of the polymer. In addition, the L segment contains fewer branches and the bond angle is relatively fixed, presenting a certain linear structure in the slurry system. The segment is fully stretched in the slurry system and is not easily entangled. The steric hindrance it produces fully isolates the solid particles and further improves the dispersion effect.
[0014] In addition, the structural units shown in Formula II and Formula III in the L segment contain ester groups and amide groups. Due to the p-π conjugation effect, the lone pair charges of the oxygen atoms and nitrogen atoms on the ester group and the amide group will be delocalized to the CO single bond and the CN single bond. At the same time, the ester group and the amide group, as carboxylic acid derivative groups, will produce enol tautomerism under acidic or alkaline conditions, and their α-C will produce a transient double bond with the C on the carbonyl group. Therefore, the entire L segment contains some double bond properties, and the L segment tends to be linear, which will reduce the sliding resistance between the positive electrode active materials during the cold pressing process, increase the flexibility of the electrode, and improve the flexibility of the electrode.
[0015] In summary, compared with existing dispersants, the polymer dispersant of the present application has wide versatility and is suitable for slurry systems containing positive electrode active materials with different degrees of graphitization. Compared with existing dispersants, the present application improves the dispersibility of the polymer through the combined action of the terminal X group, ester group, amide group and L segment, improves the applicability of the polymer dispersant for positive electrode active materials with different degrees of graphitization, and helps to reduce preparation costs and improve production efficiency.
[0016] In any embodiment, the polymer comprises at least one of the structures shown in Formula I-1, Formula I-2, Formula I-3, and Formula I-4,
[0017]
[0018]
[0019] wherein a1 and a2 are each independently an integer between 2 and 12, R 6 , R 7 Each independently contains hydrogen, C 1-12 Alkyl, C 1-12 Alkyl alcohol, *-NH-R 11 -OH, at least one, R 8 , R 9 , R 10 Each independently contains hydrogen, C 1-12 Alkyl, C 1-12 Alkyl alcohol, *-NH-R 12 -OH, At least one of the following, where R 11 , R 12 Each independently contains C 1-12 Alkylene, R 13 Contains C 1-12 Alkyl or C 6-30 Aromatic group.
[0020] In any embodiment, the polymer comprises at least one of the structures shown in Formula I-1, Formula I-2, and Formula I-4,
[0021]
[0022]
[0023] wherein a1 and a2 are each independently an integer between 2 and 12, R 6 , R 7 Each independently contains hydrogen, C 1-12 Alkyl alcohol, *-NH-R 11 -OH, at least one, R 10 Contains hydrogen, C 1-12 Alkyl alcohol, *-NH-R 12 -OH, At least one of the following, where R 11 , R 12 Each independently contains C 1-12 Alkylene, R 13 Contains C 1-12 Alkyl or C 6-30 Aromatic group.
[0024] In any embodiment, R in the structural unit represented by formula III 5 Contains hydrogen.
[0025] R in the structural unit shown in Formula III 5 Containing hydrogen, it can produce hydrogen bonds with oxygen atoms on the surface of the positive electrode active material, further increase the dispersion effect of the polymer on the slurry, increase the solid content of the slurry, slow down the gelation of the slurry, improve the flexibility of the electrode, and improve the performance of the electrode.
[0026] In any embodiment, R 1 Include R 2 Include R 3 Include R 4 Include At least one of n1, n2, n3, and n4 is 0, and m1, m2, m3, and m4 are each independently an integer between 2 and 10.
[0027] The polymer contains polyethylene oxide segments or polyethylene oxide-propylene oxide segments, which can improve the flexibility of the polymer, reduce the sliding resistance between particles during the cold pressing process of the electrode, increase the flexibility of the electrode, and improve the first coulombic efficiency and high-temperature storage performance of the battery.
[0028] In any embodiment, R 1 Include R 2 Include R 3Include R 4 Include Wherein n1, n2, n3, n4, m1, m2, m3, and m4 are each independently an integer between 1 and 10.
[0029] The polymer contains polyethylene oxide-propylene oxide chain segments, which can further improve the flexibility of the polymer, reduce the sliding resistance between particles during the cold pressing process of the pole piece, increase the flexibility of the pole piece, and improve the high-temperature storage performance of the battery.
[0030] In any embodiment, the ratio of the number of repetitions of the structural unit represented by formula II in L to the number of repetitions of the structural unit represented by formula III is 1:7-7:1.
[0031] By controlling the ratio of the repetition number of the structural unit represented by formula II in L to the repetition number of the structural unit represented by formula III within a suitable range, the polymer can effectively disperse the slurry, the slurry has a high solid content, the electrode has excellent flexibility, and the battery has excellent first coulombic efficiency and high-temperature storage performance.
[0032] In any embodiment, the ratio of the number of repetitions of the structural unit represented by formula II in L to the number of repetitions of the structural unit represented by formula III is 1:3-3:1.
[0033] By controlling the ratio of the repetition number of the structural unit represented by formula II in L to the repetition number of the structural unit represented by formula III within a suitable range, the flexibility of the electrode can be improved, the initial coulombic efficiency and high-temperature storage performance of the battery can be improved, and the electrochemical performance of the battery can be comprehensively improved.
[0034] In any embodiment, the number of repetitions of the structural unit represented by formula II in L is 8-50, and the number of repetitions of the structural unit represented by formula III in L is 8-50.
[0035] Controlling the repetition number of the structural unit shown in Formula II and the repetition number of the structural unit shown in Formula III within an appropriate range can ensure that the polymer has a sufficient number of ester groups and amide groups, which can enable the polymer to generate sufficient intermolecular induction force, form sufficient intermolecular interaction force with the solid particles in the slurry system, and improve the dispersibility of the polymer. At the same time, the appropriate number of structural units shown in Formula II and structural units shown in Formula III make the polymer have excellent solubility in the slurry system, and the polymer fully stretches in the slurry system, so that the polymer can play the role of a dispersant.
[0036] In any embodiment, X' comprises C 3-30 Alkyl, C 6-30 At least one of aromatic groups.
[0037] In any embodiment, the weight average molecular weight of the polymer is 3000 g / mol to 55000 g / mol.
[0038] In any embodiment, the polymer has a glass transition temperature of 30°C to 150°C.
[0039] In any embodiment, the polymer has a melting point of 60°C to 210°C at 1 standard atmosphere.
[0040] In any embodiment, the polymer has a hydrophilic-lipophilic balance value of 6-16.
[0041] The second aspect of the present application provides a method for preparing a polymer, the preparation method comprising the following steps:
[0042] 1) Polycondensation reaction: polymerizing at least one dibasic acid, at least one diol and at least one diamine to prepare an intermediate polymer, wherein the intermediate polymer comprises a structure shown in Formula IV,
[0043] Y′-LY Formula IV
[0044] wherein Y' and Y each independently contain at least one of a carboxyl group, a hydroxyl group, and an amino group;
[0045] 2) End group reaction: reacting the end groups of the intermediate polymer to obtain a polymer having a structure shown in formula I,
[0046] X′-LX Formula Ⅰ
[0047] X comprises at least one of a carboxyl group, an ester group, a sulfonic acid group, a sulfonate group, a phosphoric acid group, and a phosphoric acid ester group;
[0048] X' comprises a nonpolar group;
[0049] L comprises structural units represented by formula II and formula III,
[0050]
[0051]
[0052] R 1 Contains C 1-12 Alkylene, C 6-12 Aromatic group, At least one of R 2 Contains C 1-12 Alkylene, C 6-12 Aromatic group, At least one of R 3 Contains C 1-12 Alkylene, C 6-12 Aromatic group, At least one of R 4 Contains C 1-12 Alkylene, C 6-12 Aromatic group, At least one of R 5 Contains hydrogen or C 1-3 Alkyl, where EO represents -CH 2 -CH 2 -O-, PO represents -CH(CH 3 )-CH 2 -O-, m1, m2, m3, m4 are each independently an integer between 1 and 10, and n1, n2, n3, n4 are each independently an integer between 0 and 10.
[0053] The preparation method of the present application can obtain a polymer having a carboxyl group, an ester group, a sulfonic acid group, a sulfonate group, a phosphoric acid group or a phosphoric acid ester group at one end and a non-polar group at the other end, and an ester group and an amide group in the main chain. The polymer is used as a dispersant, which can be applied to positive electrode active materials with different graphitization degrees, can improve the dispersibility of the slurry system containing positive electrode active materials with different graphitization degrees, effectively increase the solid content of the slurry, slow down the gelation phenomenon of the slurry, reduce the membrane resistance of the pole piece, improve the flexibility of the pole piece, and improve the first coulomb efficiency and high temperature cycle performance of the battery.
[0054] In any embodiment, the preparation method specifically comprises:
[0055] Stirring a catalyst, at least one dibasic acid, at least one diol and at least one diamine at 20° C.-250° C. for 1 h-20 h to obtain an intermediate polymer, wherein both ends of the intermediate polymer have the same end group;
[0056] The terminal groups at both ends of the intermediate polymer are reacted respectively to obtain the polymer.
[0057] The present invention adopts polycondensation reaction and terminalization reaction to prepare the polymer, the preparation method is simple and the production efficiency is improved.
[0058] In a third aspect of the present application, a dispersant is provided, wherein the dispersant comprises the polymer of the first aspect or the polymer prepared by the preparation method of the second aspect.
[0059] The fourth aspect of the present application provides a use of the polymer of the first aspect in a secondary battery.
[0060] In a fifth aspect of the present application, a positive electrode slurry is provided, comprising a positive electrode active material, a conductive agent, a binder and a dispersant, wherein the dispersant comprises the polymer of the first aspect.
[0061] The positive electrode slurry has excellent dispersibility and high solid content, and can be used to prepare a pole piece with excellent performance.
[0062] In any embodiment, the positive electrode active material includes lithium iron phosphate having a carbon coating layer on the surface.
[0063] In any embodiment, the graphitization degree of the lithium iron phosphate having the carbon coating layer on the surface is 10%-30%.
[0064] The polymer dispersant of the present application can be applied to a slurry system using lithium iron phosphate with different graphitization degrees as a positive electrode active material, has universal applicability, and helps to reduce preparation costs and improve production efficiency.
[0065] In any embodiment, the mass fraction of the dispersant is 0.01%-3%, based on the total mass of the solid matter in the positive electrode slurry.
[0066] The mass fraction of the dispersant is within a suitable range, the slurry has a high solid content, the electrode has excellent flexibility, and the battery has excellent first coulombic efficiency and high-temperature storage performance.
[0067] In any embodiment, the mass fraction of the dispersant is 0.03%-2%, based on the total mass of the solid matter in the positive electrode slurry.
[0068] When the mass fraction of the dispersant is within an appropriate range, the flexibility of the electrode can be further improved and the performance of the electrode can be improved.
[0069] In a sixth aspect of the present application, a positive electrode plate is provided, comprising a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer is prepared from the positive electrode slurry of the fifth aspect.
[0070] The positive electrode plate of the present application has excellent flexibility and low film resistance, and the plate has excellent performance.
[0071] In a seventh aspect of the present application, a secondary battery is provided, comprising a separator, a negative electrode plate, an electrolyte, and the positive electrode plate of the sixth aspect.
[0072] In an eighth aspect of the present application, there is provided an electrical device comprising the secondary battery of the seventh aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0073] Figure 1 is a schematic diagram of a secondary battery according to an embodiment of the present application;
[0074] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown;
[0075] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application;
[0076] Figure 4 is a schematic diagram of a battery pack according to an embodiment of the present application;
[0077] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown;
[0078] Figure 6 Schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source.
[0079] Description of reference numerals:
[0080] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION
[0081] Below, the embodiments of the positive electrode active material and its manufacturing method, positive electrode sheet, secondary battery, battery module, battery pack and electrical device of the present application are specifically disclosed with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0082] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0083] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0084] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0085] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0086] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0087] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0088] The positive electrode slurry is mainly a solid-liquid phase mixed system formed by a positive electrode active material, a conductive agent, a binder and a solvent. In the prior art, a dispersant is often added to improve the dispersibility of the slurry. However, the dispersants in the prior art are usually only applicable to slurry systems with fixed components, and have poor versatility. After the physical properties of the components in the slurry change, the dispersant often needs to be adjusted. For example, the lithium iron phosphate produced under different process conditions in the prior art has different degrees of carbon coating on the surface, and the degree of graphitization of the lithium iron phosphate is different. Often, a dispersant cannot be applied to lithium iron phosphate with different degrees of graphitization. When the dispersant in the prior art is used in a slurry system with lithium iron phosphate with different degrees of graphitization as the positive electrode active material, the dispersibility of the slurry system is not ideal, and it is difficult to meet the performance requirements of the pole piece and the battery.
[0089] [Dispersant]
[0090] Based on this, the present application provides a polymer, the polymer comprising the structure shown in Formula I,
[0091] X′-LY Formula Ⅰ
[0092] wherein X comprises at least one of a carboxyl group, an ester group, a sulfonic acid group, a sulfonate group, a phosphoric acid group, and a phosphoric acid ester group;
[0093] X' comprises a nonpolar group;
[0094] L comprises structural units represented by formula II and formula III,
[0095]
[0096] Where R 1 Contains C 1-12 Alkylene, C 6-12 Aromatic group, At least one of R 2 Contains C 1-12 Alkylene, C 6-12 Aromatic group, At least one of R 3 Contains C 1-12 Alkylene, C 6-12 Aromatic group, At least one of R 4 Contains C 1-12 Alkylene, C6-12 Aromatic group, At least one of R 5 Contains hydrogen or C 1-3 alkyl,
[0097] EO represents -CH 2 -CH 2 -O-, PO represents -CH(CH 3 )-CH 2 -O-, m1, m2, m3, m4 are each independently an integer between 1 and 10, and n1, n2, n3, n4 are each independently an integer between 0 and 10.
[0098] In this context, the term "polymer" includes, on the one hand, a collection of macromolecules that are chemically uniform but differ in degree of polymerization, molar mass and chain length, prepared by polymerization. The term also includes, on the other hand, derivatives of such a collection of macromolecules formed by polymerization, i.e. compounds that can be obtained by reaction, for example addition or substitution, of functional groups in the above-mentioned macromolecules and can be chemically uniform or chemically heterogeneous.
[0099] As used herein, the term "carboxyl" refers to -COOH.
[0100] As used herein, the term "ester group" refers to R 14 A non-hydrogen group.
[0101] As used herein, the term "sulfonic acid group" refers to -SO 3 H.
[0102] As used herein, the term "sulfonate group" refers to R 15 A non-hydrogen group.
[0103] As used herein, the term "phosphate group" refers to
[0104] As used herein, the term "phosphate group" refers to R 16 A non-hydrogen group.
[0105] As used herein, the term "amide group" refers to R 17 , R 18 Each is independently hydrogen or a non-hydrogen group.
[0106] As used herein, the term "non-polar group" refers to a group in which the positive and negative charge centers coincide with each other, including but not limited to alkyl groups and aromatic groups.
[0107] As used herein, the term "alkyl" refers to a straight or branched hydrocarbon chain radical consisting solely of carbon and hydrogen atoms with no unsaturation present in the radical.
[0108] As used herein, the term "aromatic" refers to an aromatic ring system in which at least one ring is aromatic.
[0109] In some embodiments, the non-polar group includes C 3-30 Alkyl or C 6-30 Aromatic group.
[0110] In this article, the term “C 3-30 "Alkyl" refers to a straight or branched hydrocarbon chain radical consisting solely of carbon and hydrogen atoms, with no unsaturation in the radical, having from 6 to 30 carbon atoms, and attached to the remainder of the molecule by a single bond. 1-3 Alkyl" and "C 1-12 "Alkyl" should be interpreted accordingly.
[0111] In this article, the term “C 6-30 An "aromatic group" refers to a monovalent functional group formed by removing a hydrogen atom from a ring of an aromatic hydrocarbon containing 6 to 30 carbon atoms, such as a phenyl group or a naphthyl group. An aromatic hydrocarbon refers to a hydrocarbon having an aromatic ring, and includes monocyclic and polycyclic hydrocarbons, wherein the additional rings of the polycyclic hydrocarbon may be aromatic or non-aromatic.
[0112] In this article, the term “C 1-12 "Alkylene" refers to branched and straight-chain saturated aliphatic divalent hydrocarbon radicals having the specified number of carbon atoms, with no unsaturation present in the radical, having from 1 to 12 carbon atoms, and attached to the rest of the molecule by a single bond.
[0113] In this article, the term “C 6-12 The term "arylene group" refers to a divalent functional group formed by removing two hydrogen atoms from an aromatic hydrocarbon ring containing 6 to 12 carbon atoms, including but not limited to phenylene or naphthylene.
[0114] In this article, The EO units and PO units in the polymer may be arranged randomly or in blocks.
[0115] In some embodiments, R 1 and R 3 are the same.
[0116] In some embodiments, R 1 and R 3 are not the same.
[0117] In this article, the term "dispersant" refers to a type of substance that prevents solid particles from aggregating with each other in a solid-liquid dispersion system and allows the solid particles to remain uniformly dispersed in the liquid phase for a longer period of time.
[0118] In some embodiments, the dispersion medium of the dispersant is an aqueous solvent, such as water, that is, the dispersant is dissolved in the aqueous solvent.
[0119] In some embodiments, the dispersion medium of the dispersant is an oily solvent, and examples of the oily solvent include but are not limited to dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, acetone, dimethyl carbonate, ethyl cellulose, and polycarbonate. That is, the dispersant is dissolved in the oily solvent.
[0120] In some embodiments, the dispersant is used as a positive electrode slurry dispersant, and is used to disperse the positive electrode active material, the conductive agent, and the binder to form a positive electrode slurry.
[0121] In some embodiments, the dispersant is used as a negative electrode slurry dispersant, and is used to disperse the negative electrode active material, the conductive agent, and the binder to form a negative electrode slurry.
[0122] In some embodiments, the X group comprises a carboxyl group, a sulfonic acid group, or a phosphate group.
[0123] The carboxyl group, sulfonic acid group or phosphoric acid group can be ionized to generate negative ions, which are adsorbed on the surface of the positive electrode active material particles in the slurry system mainly through electrostatic action, anchoring one end of the polymer on the surface of the positive electrode active material particles.
[0124] In some embodiments, the X group comprises an ester group, a sulfonate group, or a phosphate group.
[0125] The ester group, sulfonate group or phosphate group is adsorbed on the surface of the positive electrode active material particles in the slurry system through intermolecular forces, and one end of the polymer is anchored on the surface of the positive electrode active material particles.
[0126] The end group of one end of the polymer contains a non-polar group, which is lipophilic, and the end group of the other end contains at least one of carboxyl, ester, sulfonic acid, sulfonate, phosphoric acid, and phosphate, which is a polar group and is hydrophilic. When the polymer is added to the slurry system, the carboxyl, ester, sulfonic acid, sulfonate, phosphoric acid, or phosphate at one end is adsorbed on the surface of the positive electrode active material particles as an anchor point, and the other end is suspended in the slurry to form a steric barrier. When the particles approach each other, this steric barrier will produce a strong repulsive force, preventing the particles from agglomerating and forming a uniformly dispersed and stable slurry. The structural units shown in Formula II and Formula III contain ester and amide groups, both of which are polar groups, which can produce strong intermolecular induction forces, form strong intermolecular forces with the particles, and further improve the dispersion ability of the polymer. In addition, the oxygen and nitrogen atoms in the ester group and the amide group can form hydrogen bonds with the hydroxyl and / or carboxyl groups on the surface of the positive electrode active material, and the oxygen and nitrogen atoms can form coordination with the positive electrode active material, and jointly enhance the dispersion of the particles in the slurry system by the polymer dispersant. The L segment contains fewer side chains, and the bond angle is relatively fixed, presenting a certain linear structure in the slurry system. The L segment is fully stretched in the slurry system, and it is not easy to entangle between the segments. The steric hindrance generated by it fully isolates each solid particle, and the full extension of the L segment also makes the ester group and the amide group fully interact with different particles, further improving the dispersion effect. The polymer dispersant of the present application can achieve multi-site adsorption on the surface of the positive electrode active material with different graphitization degrees, so that the adsorption effect is more significant, and the dispersion effect of the polymer dispersant on the slurry is enhanced.
[0127] In addition, the structural units shown in Formula II and Formula III in the L segment contain ester groups and amide groups. Due to the p-π conjugation effect, the lone pair charges of the oxygen atoms and nitrogen atoms on the ester group and the amide group will be delocalized to the CO single bond and the CN single bond. At the same time, the ester group and the amide group, as carboxylic acid derivative groups, will produce enol tautomerism under acidic or alkaline conditions, and their α-C will produce a transient double bond with the C on the carbonyl group. Therefore, the entire L segment contains some double bond properties, and the L segment tends to be linear, which will reduce the sliding resistance between the positive electrode active materials during the cold pressing process, increase the flexibility of the electrode, and improve the flexibility of the electrode.
[0128] In summary, the polymer of the present application, as a dispersant, can improve the dispersibility of the slurry containing positive electrode active materials with different graphitization degrees under the action of multi-site adsorption, effectively increase the solid content of the slurry, slow down the gelation of the slurry, reduce the membrane resistance of the pole piece, and improve the first coulomb efficiency and high-temperature cycle performance of the battery. At the same time, it can also improve the flexibility of the pole piece, providing a basis for the subsequent preparation of thick-coated high-voltage dense pole pieces.
[0129] The dispersants in the prior art have poor compatibility and cannot adapt to the differences in positive electrode active materials produced under different process conditions in the slurry. The present application improves the dispersibility of the polymer through the combined action of the terminal X group, ester group, amide group and L segment, improves the applicability of the polymer dispersant for positive electrode active materials with different graphitization degrees, improves the universality of the polymer dispersant, and helps to reduce the preparation cost and improve the production efficiency.
[0130] In some embodiments, the polymer comprises at least one of the structures shown in Formula I-1, Formula I-2, Formula I-3, and Formula I-4.
[0131]
[0132] wherein a1 and a2 are each independently an integer between 2 and 12, R 6 , R 7 Each independently contains hydrogen, C 1-12 Alkyl, C 1-12 Alkyl alcohol, *-NH-R 11 -OH, at least one, R 8 , R 9 , R 10 Each independently contains hydrogen, C 1-12 Alkyl, C 1-12 Alkyl alcohol, *-NH-R 12 -OH, At least one of the following, where R 11 , R 12 Each independently contains C 1-12 Alkylene, R 13 Contains C 1-12 Alkyl or C 6-30 Aromatic group.
[0133] In this article, the term “C 1-12 "Alkyl alcohol" refers to a monovalent atomic group of an alkylene group bonded to a hydroxyl group (-OH) and consisting of "-C n H 2n -OH" (wherein n is a natural number from 1 to 12).
[0134] In some embodiments, the polymer comprises at least one of the structures shown in Formula I-1, Formula I-2, and Formula I-4.
[0135]
[0136] wherein a1 and a2 are each independently an integer between 2 and 12, R 6 , R 7 Each independently contains hydrogen, C 1-12 Alkyl alcohol, *-NH-R11 -OH, at least one, R 10 Contains hydrogen, C 1-12 Alkyl alcohol, *-NH-R 12 -OH, At least one of the following, where R 11 , R 12 Each independently contains C 1-12 Alkylene, R 13 Contains C 1-12 Alkyl or C 6-30 Aromatic group.
[0137] In some embodiments, R in the structure shown in Formula I-1 6 Contains hydrogen.
[0138] R 6 Containing hydrogen, the polymer can be ionized to produce negative ions, which can be adsorbed on the surface of the positive electrode active material particles in the slurry system through electrostatic action, thereby enhancing the dispersion effect of the polymer dispersant, increasing the solid content of the slurry, slowing down the gelation of the slurry, improving the flexibility of the electrode, and improving the performance of the slurry and the electrode.
[0139] In some embodiments, R in the structure shown in Formula I-1 6 Contains C 1-12 Alkyl alcohol or *-NH-R 11 OH.
[0140] R 6 Contains C 1-12 Alkyl alcohol or *-NH-R 11 -OH, wherein the amino group or hydroxyl group can generate adsorption force with the positive electrode active material particles in the slurry system, enhance the dispersing effect of the polymer dispersant, increase the solid content of the slurry, and improve the performance of the slurry.
[0141] In some embodiments, R in the structure shown in Formula I-2 7 Contains hydrogen.
[0142] R 7 Containing hydrogen, the polymer can be ionized to produce negative ions, which can be adsorbed on the surface of the positive electrode active material particles in the slurry system through electrostatic action, thereby enhancing the dispersion effect of the polymer dispersant, increasing the solid content of the slurry, slowing down the gelation of the slurry, improving the flexibility of the electrode, reducing the membrane resistance of the electrode, and improving the high-temperature cycle performance of the battery.
[0143] In some embodiments, R in the structure shown in Formula I-2 7 Contains C 1-12 Alkyl alcohol or *-NH-R 11 -OH.
[0144] R 7 Contains C 1-12 Alkyl alcohol or *-NH-R 11 -OH, the amino or hydroxyl groups can generate adsorption force with the positive electrode active material particles in the slurry system, enhance the dispersion effect of the polymer dispersant, increase the solid content of the slurry, slow down the gelation of the slurry, improve the flexibility of the electrode, reduce the diaphragm resistance of the electrode, and improve the first coulomb efficiency and high-temperature cycle performance of the battery.
[0145] In some embodiments, R in the structure shown in Formula I-3 8 or R 9 Contains hydrogen.
[0146] R 8 or R 9 Containing hydrogen, the polymer can be ionized to produce negative ions, which can be adsorbed on the surface of the positive electrode active material particles in the slurry system through electrostatic action, enhancing the dispersion effect of the polymer dispersant, slowing down the gelation phenomenon of the slurry, improving the flexibility of the electrode, and improving the first coulomb efficiency and high-temperature cycle performance of the battery.
[0147] In some embodiments, R in the structure shown in Formula I-3 8 or R 9 Contains C 1-12 Alkyl alcohol, *-NH-R 12 -OH, At least one of .
[0148] R 8 or R 9 Contains C 1-12 Alkyl alcohol, *-NH-R 12 -OH or The amino, hydroxyl and ester groups can generate adsorption force with the positive electrode active material particles in the slurry system, enhance the dispersing effect of the polymer dispersant, increase the solid content of the slurry, and improve the performance of the slurry.
[0149] In some embodiments, R in the structure shown in Formula I-4 10 Contains hydrogen.
[0150] R 10 Containing hydrogen, the polymer can be ionized to generate negative ions, which can be adsorbed on the surface of the positive electrode active material particles in the slurry system through electrostatic action, thereby enhancing the dispersing effect of the polymer dispersant, increasing the solid content of the slurry, and improving the performance of the slurry.
[0151] In some embodiments, R in the structure shown in Formula I-4 10 Contains C 1-12 Alkyl alcohol, *-NH-R 12-OH, At least one of .
[0152] R 10 Contains C 1-12 Alkyl alcohol, *-NH-R 12 -OH or The amino, hydroxyl and ester groups can generate adsorption force with the positive electrode active material particles in the slurry system, enhance the dispersing effect of the polymer dispersant, increase the solid content of the slurry, and improve the performance of the slurry.
[0153] In some embodiments, the polymer comprises the structure shown in Formula I-4.
[0154] Compared with the structure shown in Formula Ⅰ-3 which contains one L segment, the structure shown in Formula Ⅰ-4 contains two L segments, which can enhance the dispersing effect of the polymer dispersant, make the slurry have a high solid content, improve the flexibility of the electrode, improve the first coulombic efficiency of the battery, and improve the electrochemical performance of the battery.
[0155] In some embodiments, R in the structural unit represented by Formula III 5 Contains hydrogen.
[0156] R in the structural unit shown in Formula III 5 Containing hydrogen can produce hydrogen bonds with oxygen atoms on the surface of the positive electrode active material, which can further improve the dispersibility of the slurry, increase the solid content of the slurry, slow down the gelation of the slurry, improve the flexibility of the electrode, and improve the performance of the electrode.
[0157] In some embodiments, R 1 Contains C 1-12 Alkylene or R 2 Contains C 1-12 Alkylene or R 3 Contains C 1-12 Alkylene or R 4 Contains C 1-12 Alkylene or
[0158] m1, m2, m3, and m4 are each independently an integer between 1 and 10, and n1, n2, n3, and n4 are each independently an integer between 0 and 10.
[0159] Introducing a longer alkyl segment or a flexible polyether segment into the L segment can improve the flexibility of the electrode.
[0160] In some embodiments, R 1 Include R 2 Include R 3 Include R 4 Include At least one of n1, n2, n3, and n4 is 0, and m1, m2, m3, and m4 are each independently an integer between 2 and 10.
[0161] In this context, the term "polyoxyethylene segment" refers to a polyoxyethylene segment comprising -CH 2 -CH 2 -O- structural unit polymer chain segment.
[0162] In this context, the term "polyoxyethylene-oxypropylene segment" refers to a segment comprising -CH 2 -CH 2 -O- and -CH(CH 3 )-CH 2 -O- structural unit polymer chain segment.
[0163] The polymer contains polyethylene oxide chain segments or polyethylene oxide-propylene oxide chain segments, which can improve the flexibility of the polymer, reduce the sliding resistance between particles during the cold pressing process of the pole piece, increase the flexibility of the pole piece, and improve the performance of the pole piece.
[0164] In some embodiments, R 1 Include R 2 Include R 3 Include R 4 Include Wherein n1, n2, n3, n4, m1, m2, m3, and m4 are each independently an integer between 1 and 10.
[0165] The polymer contains polyethylene oxide-propylene oxide chain segments, which can further improve the flexibility of the polymer, reduce the sliding resistance between particles during the cold pressing process of the pole piece, improve the flexibility of the pole piece, improve the performance of the pole piece, and improve the high-temperature storage performance of the battery.
[0166] In some embodiments, the ratio of the number of repetitions of the structural unit represented by formula II in L to the number of repetitions of the structural unit represented by formula III is 1:7-7:1.
[0167] In some embodiments, the ratio of the number of repetitions of the structural unit represented by formula II in L to the number of repetitions of the structural unit represented by formula III can be selected as any value of 1:7, 1:6, 1:5, 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, or a range consisting of any two values thereof.
[0168] The ratio of the repetition number of the structural unit shown in Formula II to the repetition number of the structural unit shown in Formula III is within a suitable range, the slurry has a high solid content, the electrode has excellent flexibility, and the battery has excellent first coulombic efficiency and high-temperature storage performance.
[0169] In some embodiments, the ratio of the number of repetitions of the structural unit represented by formula II in L to the number of repetitions of the structural unit represented by formula III is 1:3-3:1.
[0170] In some implementations, the ratio of the number of repetitions of the structural unit represented by formula II in L to the number of repetitions of the structural unit represented by formula III can be selected as any value of 1:3, 1:2, 1:1, 2:1, 3:1, or a range consisting of any two values thereof.
[0171] By controlling the ratio of the number of repetitions of the structural unit represented by Formula II in L to the number of repetitions of the structural unit represented by Formula III within a suitable range, the flexibility of the electrode can be improved, and the first coulombic efficiency and high-temperature storage performance of the battery can be improved.
[0172] In some embodiments, the number of repetitions of the structural unit represented by formula II in L is 8-50, and the number of repetitions of the structural unit represented by formula III in L is 8-50.
[0173] In some embodiments, the number of repetitions of the structural unit represented by Formula II in L can be selected as any value among 8, 10, 20, 30, 40, 50 or a range consisting of any two values therein.
[0174] In some embodiments, the number of repetitions of the structural unit represented by Formula III in L can be selected as any value among 8, 10, 20, 30, 40, 50, or a range consisting of any two values therein.
[0175] Controlling the repetition number of the structural unit shown in Formula II and the repetition number of the structural unit shown in Formula III within an appropriate range can ensure that the polymer has a sufficient number of ester groups and amide groups, can ensure that the polymer generates sufficient intermolecular induction force, forms sufficient intermolecular interaction force with the solid particles in the slurry system, and improves the dispersibility of the polymer. At the same time, the appropriate number of structural units shown in Formula II and structural units shown in Formula III makes the polymer have excellent solubility in the slurry system, and the polymer fully stretches in the slurry system, so that the polymer can play the role of a dispersant.
[0176] In some embodiments, the mass percentage of X in the polymer is 0.5%-5% based on the mass of the polymer.
[0177] In some embodiments, based on the mass of the polymer, R 1 , R 2 , R 3 With R 4The total mass percentage is 50%-80%.
[0178] In some embodiments, based on the mass of the polymer, the The mass percentage is 5%-20%.
[0179] Control X group, R 1 , R 2 , R 3 With R 4 The mass percentages of the ester group and the amide group are within a suitable range, so that the X anchoring group, the L segment, the ester group and the amide group can give full play to their respective advantages, and work together to make the polymer have excellent dispersibility and improve the dispersibility of the slurry.
[0180] In some embodiments, the weight average molecular weight of the polymer is 3000 g / mol to 55000 g / mol.
[0181] In some embodiments, the weight average molecular weight of the polymer can be selected as any value of 3000 g / mol, 3500 g / mol, 4000 g / mol, 4500 g / mol, 5000 g / mol, 5500 g / mol, 6000 g / mol, 6500 g / mol, 7000 g / mol, 7500 g / mol, 8000 g / mol, 8500 g / mol, 9000 g / mol, 9500 g / mol, 10000 g / mol, 15000 g / mol, 20000 g / mol, 25000 g / mol, 30000 g / mol, 35000 g / mol, 40000 g / mol, 45000 g / mol, 50000 g / mol, 55000 g / mol, or a range consisting of any two of the values.
[0182] In some embodiments, the weight average molecular weight of the polymer is 6000 g / mol to 30000 g / mol.
[0183] In some embodiments, the weight average molecular weight of the polymer can be selected as any value of 6000 g / mol, 6500 g / mol, 7000 g / mol, 7500 g / mol, 8000 g / mol, 8500 g / mol, 9000 g / mol, 9500 g / mol, 10000 g / mol, 15000 g / mol, 20000 g / mol, 25000 g / mol, 30000 g / mol, or a range consisting of any two values thereof.
[0184] As used herein, the term "weight average molecular weight" refers to the sum of the products of the weight fractions of molecules with different molecular weights in a polymer and their corresponding molecular weights.
[0185] In the present application, the weight average molecular weight of the polymer can be tested by methods known in the art, such as gel chromatography, such as using a Waters 2695 Isocratic HPLC gel chromatograph (differential refractive index detector 2141) for testing. In some embodiments, the test method is to use a polystyrene solution sample with a mass fraction of 3.0% as a reference, and select a matching chromatographic column (oily: Styragel HT5DMF7.8*300mm+Styragel HT4). Use purified N-methylpyrrolidone (NMP) solvent to prepare a 3.0% fluorine-containing polymer solution, and let the prepared solution stand for one day for use. During the test, first use a syringe to draw tetrahydrofuran, rinse, and repeat several times. Then draw 5 ml of the experimental solution, expel the air in the syringe, and wipe the needle tip dry. Finally, slowly inject the sample solution into the injection port. After the reading stabilizes, obtain the data and read the weight average molecular weight.
[0186] If the weight average molecular weight of the polymer is too large, the polymer is difficult to dissolve and cannot act as a dispersant. If the weight average molecular weight of the polymer is too small, it cannot play an effective dispersing role, which is not conducive to the formation of a conductive network, resulting in an increase in the film resistance of the electrode, and a decrease in the first coulomb efficiency and high-temperature storage performance of the battery.
[0187] In some embodiments, the polymer has a glass transition temperature of 30°C to 150°C.
[0188] In some embodiments, the glass transition temperature of the polymer is any value of 30°C, 60°C, 90°C, 100°C, 120°C, 140°C, 150°C, or a range consisting of any two of these values.
[0189] In this article, the term "glass transition temperature" refers to the transition temperature of an amorphous polymer (including the non-crystalline part of a crystalline polymer) from a glassy state to an elastic state or from an elastic state to a glassy state, and is the lowest temperature at which the macromolecular chains of an amorphous polymer can move freely.
[0190] In this article, the term "glassy state" refers to the state in which amorphous polymers change very little under the action of external forces, the deformation is proportional to the magnitude of the force, and the deformation can be restored immediately after the external force is removed. In the glassy state, the energy of molecular motion is very low, insufficient to overcome the barrier of rotation within the main chain, insufficient to stimulate the movement of the chain segments, and the chain segments are in a frozen state. For example, when subjected to external force, since the movement of the chain segments is frozen, only the bond length and bond angle of the main chain can be slightly changed. Therefore, from a macroscopic point of view, the deformation of the polymer after the force is very small.
[0191] In this article, the term "high elastic state" refers to the amorphous polymer that undergoes a large deformation under a very small external force. In the high elastic state, when the amorphous polymer is subjected to an external force, the molecular chain adapts to the external force through the internal rotation of single bonds and the change of conformation of chain segments. For example, when subjected to a tensile force, the molecular chain can change from a curled state to an extended state, so that a large deformation can occur macroscopically. Once the external force is removed, the molecular chain will return to the original curled state through the internal rotation of single bonds and the movement of chain segments, which is manifested as elastic retraction macroscopically.
[0192] In the present application, the glass transition temperature of the polymer can be tested by methods known in the art, such as using a differential scanning calorimeter (Q1000) of TA Company to test the glass transition temperature. Take 6-9g of polymer sample, heat it from room temperature to 200℃ at a heating rate of 10℃ / min, analyze the obtained differential scanning calorimetry curve, and the glass transition temperature of the polymer can be obtained in ℃.
[0193] In some embodiments, the polymer has a melting point of 60°C to 210°C at 1 standard atmosphere.
[0194] In some embodiments, the melting point of the polymer at 1 standard atmosphere is any value of 60°C, 80°C, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 210°C, or a range consisting of any two of them.
[0195] In this article, the term "1 standard atmosphere" refers to the air pressure at sea level under standard atmospheric conditions, which is 101.325 kPa and is the unit of pressure, recorded as atm.
[0196] In the present application, the melting point of a polymer under 1 standard atmosphere can be tested by methods known in the art, such as using a precision microscopic melting point tester (Model X-5) to test the melting point. Under a standard atmosphere, take 0.01 mg of uniformly ground sample and place it on a glass slide, cover it with another layer of glass slide and gently compact it, and place it in the center of the hot stage. After covering with a heat insulation board, adjust the focus of the microscope until the sample can be clearly observed. Then adjust the temperature knob, quickly raise the temperature until the polymer melts slightly, and then slowly adjust the heating rate until the sample is completely melted, and record the full melting temperature as the melting point of the polymer in ° C.
[0197] In some embodiments, the polymer has a hydrophilic-lipophilic balance value of 6-16.
[0198] In some embodiments, the hydrophilic-lipophilic balance value of the polymer may be selected as any value of 6, 8, 10, 12, 14, 16, or a range consisting of any two values thereof.
[0199] In this article, the term "hydrophile-lipophile balance value" is used to characterize the comprehensive hydrophilic-lipophilic tendency of a polymer. The larger the hydrophile-lipophile balance value, the better the hydrophilicity of the polymer. Conversely, the smaller the hydrophile-lipophile balance value, the worse its hydrophilicity and the better its lipophilicity.
[0200] In this article, the test of the hydrophilic-lipophilic balance (HLB) of the polymer can be carried out by a method known in the art, such as the emulsification method, the principle of which is that when the polymer is used to emulsify the oily medium, when the HLB value of the polymer is the same as the HLB value required by the oil phase medium, the generated emulsion has the best stability. The ideal HLB value can be obtained by mixing the standard sample with a known HLB value in proportion, emulsifying the prepared oil phase with the polymer, and letting it stand for 24 hours. The HLB value required by the oil phase in the sample with the best stability is the HLB value of the polymer.
[0201] In some embodiments, the polymer has a hydrophilic-lipophilic balance value of 10-12.
[0202] In some embodiments, the hydrophilic-lipophilic balance value of the polymer may be any value selected from 10, 11, 12, or a range consisting of any two values therein.
[0203] One embodiment of the present application provides a method for preparing a polymer, the preparation method comprising the following steps:
[0204] 1) Polycondensation reaction: polymerizing at least one dibasic acid, at least one diol and at least one diamine to prepare an intermediate polymer, wherein the intermediate polymer comprises a structure shown in Formula IV,
[0205] Y′-LY Formula IV
[0206] wherein Y' and Y each independently contain at least one of a carboxyl group, a hydroxyl group, and an amino group;
[0207] 2) End group reaction: reacting the end groups of the intermediate polymer to obtain a polymer having a structure shown in formula I,
[0208] X′-LX Formula Ⅰ
[0209] X comprises at least one of a carboxyl group, an ester group, a sulfonic acid group, a sulfonate group, a phosphoric acid group, and a phosphoric acid ester group;
[0210] X' comprises a nonpolar group;
[0211] L comprises structural units represented by formula II and formula III,
[0212]
[0213] Where R 1 Contains C 1-12 Alkylene, C6-12 Aromatic group, At least one of R 2 Contains C 1-12 Alkylene, C 6-12 Aromatic group, At least one of R 3 Contains C 1-12 Alkylene, C 6-12 Aromatic group, At least one of R 4 Contains C 1-12 Alkylene, C 6-12 Aromatic group, At least one of R 5 Contains hydrogen or C 1-3 Alkyl, where EO represents -CH 2 -CH 2 -O-, PO represents -CH(CH 3 )-CH 2 -O-, m1, m2, m3, m4 are each independently an integer between 1 and 10, and n1, n2, n3, n4 are each independently an integer between 0 and 10.
[0214] As used herein, the term "diamine" refers to an amine containing two amino groups.
[0215] As used herein, the term "diacid" refers to an acid containing two carboxyl groups.
[0216] As used herein, the term "diol" refers to an alcohol containing two hydroxyl groups.
[0217] In some embodiments, the diamine has a structure as shown in Formula V,
[0218]
[0219] Where R 4 Contains C 1-12 Alkylene, C 6-12 Aromatic group, At least one of R 5 Hydrogen or C 1-3 Alkyl, m4 is any integer between 1-10, and n4 is any integer between 0-10.
[0220] In some embodiments, the diamine comprises
[0221]
[0222] Any one of .
[0223] In any embodiment, the diol has a structure as shown in Formula VI,
[0224] HO-R 2 -OH Formula VI
[0225] Where R 2 Contains C 1-12 Alkylene, C 6-12 Aromatic group, At least one of, m2 is any integer between 1-10, and n2 is any integer between 0-10.
[0226] In some embodiments, the diol comprises
[0227]
[0228] Any one of .
[0229] In some embodiments, the dibasic acid has a structure shown in Formula VII or Formula VIII,
[0230]
[0231] Where R 1 Contains C 1-12 Alkylene, C 6-12 Aromatic group, At least one of R 3 Contains C 1-12 Alkylene, C 6-12 Aromatic group, At least one of, m1, m3 are each independently an integer between 1-10, n1, n3 are each independently an integer between 0-10.
[0232] In some embodiments, the dibasic acid comprises
[0233]
[0234] Any one of .
[0235] The preparation method has cheap raw materials, can reduce costs, reduce environmental pollution, and is conducive to increasing the output of polymer dispersants. At the same time, the preparation method can obtain a polymer containing a polar group of a carboxyl group, an ester group, a sulfonic acid group, a sulfonate group, a phosphoric acid group or a phosphoric acid ester group at one end, a non-polar group at one end, and an ester group and an amide group in the main chain. Using the polymer as a dispersant can be applied to positive electrode active materials with different graphitization degrees, can improve the dispersibility of the slurry system containing positive electrode active materials with different graphitization degrees, can effectively increase the solid content of the slurry, slow down the gelation phenomenon of the slurry, reduce the membrane resistance of the pole piece, improve the flexibility of the pole piece, and improve the first coulomb efficiency and high temperature cycle performance of the battery.
[0236] In some embodiments, the preparation method specifically comprises:
[0237] Stirring a catalyst, at least one dibasic acid, at least one diol and at least one diamine at 20° C.-250° C. for 1 h-20 h to obtain an intermediate polymer, wherein both ends of the intermediate polymer have the same end group;
[0238] The terminal groups at both ends of the intermediate polymer are reacted respectively to obtain the polymer.
[0239] In some embodiments, the terminal groups at both ends of the intermediate polymer are carboxyl groups.
[0240] In some embodiments, the terminal groups at both ends of the intermediate polymer are hydroxyl groups.
[0241] In some embodiments, the terminal groups at both ends of the intermediate polymer are amino groups.
[0242] In some embodiments, the synthetic route of the polymer is that at least one dibasic acid, at least one diol and at least one diamine undergo polymerization reaction under the action of a catalyst to generate an intermediate polymer, so that the dibasic acid, diamine or diol is excessive, and the end groups at both ends are amino, carboxyl or hydroxyl, the amino, carboxyl or hydroxyl at one end reacts with the active monomer containing the X' group, and the amino, carboxyl or hydroxyl at the other end reacts with the active monomer containing the X group to prepare a polymer containing the X group at one end and X' at the other end. It is understood that the active monomer containing the X' group refers to a monomer containing the X' group and containing an active functional group that can react with the amino, carboxyl or hydroxyl at one end of the intermediate polymer. The active monomer containing the X group refers to a monomer containing the X group and containing an active functional group that can react with the amino, carboxyl or hydroxyl at one end of the intermediate polymer. The active functional group that reacts with the amino group can be selected from any one of the epoxy group, carboxyl group, acid anhydride, isocyanate group, carbonyl chloride, and halogen atom; the active functional group that reacts with the carboxyl group can be selected from hydroxyl group or amino group; the active functional group that reacts with the hydroxyl group can be selected from any one of the epoxy group, carboxyl group, amino group, isocyanate group, halogen atom, and acid anhydride.
[0243] In some embodiments, the terminal group of the intermediate polymer is a hydroxyl group, and the reactive monomer containing an X' group refers to a reactive monomer containing an X' group and a halogen atom.
[0244] In some embodiments, the terminal group of the intermediate polymer is a hydroxyl group, and the reactive monomer containing an X group refers to a reactive monomer containing an X group and a halogen atom.
[0245] In some embodiments, the terminal group of the intermediate polymer is a hydroxyl group, and the reactive monomer containing the X' group refers to X'-(CH 2 )mA, wherein m is an integer between 1 and 12, and A is F, Cl, Br or I.
[0246] In some embodiments, the terminal group of the intermediate polymer is a hydroxyl group, and the reactive monomer containing the X group refers to X-(CH 2 )nB, wherein n is an integer between 1 and 12, and B is F, Cl, Br or I.
[0247] In some embodiments, the catalyst comprises n-butyl titanate.
[0248] The present invention adopts polycondensation reaction and terminalization reaction to prepare the polymer, the preparation method is simple and the production efficiency is improved.
[0249] In some embodiments, a dispersant is provided, wherein the dispersant includes the polymer in any embodiment or the polymer prepared by the preparation method in any embodiment.
[0250] In some embodiments, use of the polymer of any embodiment in a secondary battery is provided.
[0251] [Cathode slurry]
[0252] In some embodiments, a positive electrode slurry is provided, including a positive electrode active material, a conductive agent, a binder, and a dispersant, wherein the dispersant includes the polymer in any embodiment.
[0253] The positive electrode slurry has excellent dispersibility and high solid content, which is conducive to the preparation of pole pieces with excellent performance.
[0254] In some embodiments, the positive electrode active material may adopt a positive electrode active material for a battery that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxides (such as LiCoO 2 ), lithium nickel oxide (such as LiNiO 2 ), lithium manganese oxide (such as LiMnO 2 、LiMn 2 O 4 ), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co1 / 3 Mn 1 / 3 O 2 (Also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O 2 (Also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O 2 (Also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O 2 (Also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O 2 (Also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O 2 ) and its modified compounds, etc. Examples of lithium phosphates containing olivine structures may include, but are not limited to, lithium iron phosphate (such as LiFePO 4 (also referred to as LFP), composite materials of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO 4 ), at least one of a composite material of lithium manganese phosphate and carbon, a composite material of lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0255] In some embodiments, the positive electrode slurry includes a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0256] In some embodiments, the positive electrode active material includes lithium iron phosphate having a carbon coating layer on the surface.
[0257] On the one hand, the L segment contains ester groups and amide groups, and the oxygen atoms and nitrogen atoms on the ester groups and amide groups can coordinate with the iron atoms in the lithium iron phosphate. On the other hand, the oxygen atoms and nitrogen atoms on the ester groups and amide groups can hydrogen bond with the carboxyl groups or hydroxyl groups in the carbon coating layer. The two work together to improve the dispersion ability of the polymer on the slurry, so that the polymer dispersant has excellent dispersion ability for the slurry system with lithium iron phosphate having a carbon coating layer on the surface as the positive electrode active material.
[0258] In some embodiments, the graphitization degree of the lithium iron phosphate having a carbon coating layer on the surface is 10%-30%.
[0259] In some embodiments, the graphitization degree of the lithium iron phosphate having a carbon coating layer on the surface may be any value selected from 10%, 15%, 20%, 25%, 30%, or a range consisting of any two values thereof.
[0260] In the present application, the term "degree of graphitization" refers to the degree of graphitization of the carbon component, reflecting the completeness of the graphite crystal structure in the carbon coating layer of the carbon-coated lithium iron phosphate, that is, the regularity of the arrangement of carbon atoms in the graphite structure.
[0261] In this article, the graphitization degree of lithium iron phosphate can be tested by methods known in the art, such as using a Raman spectrometer for characterization. Specifically, the graphitization degree is characterized by a French HORIBA Jobin Yvon high-resolution Raman spectrometer, model LabRAM HR Evlution, and the following Gaussian function is used for fitting after deducting the detection background. Raman spectrum test conditions: wavelength 532nm, scanning range 200-4000cm -1 , accumulate twice, measure 10 points for each sample, and take the average value for fitting:
[0262]
[0263] In the above formula, G is the degree of graphitization, Ai, Vi and wi are the peak intensity, peak position and peak width respectively.
[0264] In order to improve the electronic and ionic conductivity of lithium iron phosphate in the prior art, carbon coating is performed on the surface of lithium iron phosphate. However, there are many types of lithium iron phosphate coating processes on the existing market, and the degree of surface carbon coating varies. The degree of graphitization of lithium iron phosphate varies. The existing dispersants are not applicable to slurries with lithium iron phosphate with different graphitization degrees as positive electrode active materials. The polymer dispersant of the present application has universality, which can improve the dispersibility of slurries with lithium iron phosphate with different graphitization degrees as positive electrode active materials, increase the solid content of the slurry, slow down the gelation phenomenon of the slurry, reduce the membrane resistance of the pole piece, improve the flexibility of the pole piece, and improve the first coulomb efficiency and high temperature cycle performance of the battery. The polymer dispersant has universality for positive electrode slurries of lithium iron phosphate with different graphitization degrees produced by different processes, which helps to reduce preparation costs and improve production efficiency.
[0265] In some embodiments, the mass fraction of the dispersant is 0.01%-3%, based on the total mass of the solid matter in the positive electrode slurry.
[0266] In some embodiments, based on the total mass of solid matter in the positive electrode slurry, the mass fraction of the dispersant can be selected as any value of 0.01%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or a range consisting of any two values thereof.
[0267] The mass fraction of the dispersant is within a suitable range, the slurry has a high solid content, the electrode has excellent flexibility, and the battery has excellent first coulombic efficiency and high-temperature storage performance.
[0268] In some embodiments, the mass fraction of the dispersant is 0.03%-2%, based on the total mass of the solid matter in the positive electrode slurry.
[0269] In some embodiments, based on the total mass of solid matter in the positive electrode slurry, the mass fraction of the dispersant can be selected as any value of 0.03%, 0.1%, 0.5%, 1%, 1.5%, 2% or a range consisting of any two values thereof.
[0270] When the mass fraction of the dispersant is within an appropriate range, the flexibility of the electrode can be further improved and the performance of the electrode can be improved.
[0271] [Positive electrode]
[0272] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer is prepared from the positive electrode slurry in any embodiment.
[0273] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0274] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0275] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder, the dispersant and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0276] [Negative electrode]
[0277] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0278] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0279] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0280] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0281] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0282] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0283] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0284] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0285] [Electrolytes]
[0286] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0287] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0288] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0289] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0290] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0291] [Isolation film]
[0292] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0293] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0294] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0295] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0296] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0297] [Secondary battery]
[0298] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example. The secondary battery may also be a sodium ion battery, a magnesium ion battery, or a potassium ion battery.
[0299] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0300] [Battery module]
[0301] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0302] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0303] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0304] [Battery Pack]
[0305] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0306] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0307] [Electrical devices]
[0308] In one embodiment of the present application, there is provided an electric device, comprising at least one of a secondary battery of any embodiment, a battery module of any embodiment, or a battery pack of any embodiment.
[0309] The electrical device includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0310] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.
[0311] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0312] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0313] Example
[0314] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0315] 1. Preparation method
[0316] Example 1
[0317] 1) Preparation of intermediate polymer: dibasic acid, diol and diamine were weighed at a molar ratio of 2:1.2:1, added into a three-necked flask, and heated to 60° C. in a water bath to melt the above monomers. The structural formulas of dibasic acid, diol and diamine are shown below:
[0318] Dibasic Acid
[0319] Diols
[0320] Diamine
[0321] A large amount of nitrogen is introduced into the reaction system, and the system is heated to 140°C, and then heated to 195°C at a rate of 30°C / h. Then, 1% of the total mass of the above-mentioned monomers in the form of propylene glycol and 0.25% of the total mass of the above-mentioned monomers in the form of catalyst n-butyl titanate are added, and stirred for 20 minutes. Then, a vacuum pump and a pressure regulating valve are used to gradually reduce the pressure of the reaction system to 60Pa. After reaching the maximum vacuum degree, the system is heated to 225°C. After reacting for 2.5 hours, the system is cooled to 200°C. After the pressure inside and outside the reaction device is equalized, the material is discharged to obtain an intermediate polymer with hydroxyl groups at both ends.
[0322] 2) End group reaction: 2 mol of the intermediate polymer with both end groups being hydroxyl groups and 1 mol of 1-chlorododecane were dissolved in 1000 ml of dichloromethane, and a halogenation reaction was carried out at room temperature. After 6 hours of reaction, 500 ml of deionized water was added to quench the reaction. The reaction mixture was extracted three times with dichloromethane, the oil phase product was collected, and then dried with magnesium sulfate, the product was separated by rotary evaporation, and finally separated by chromatography to obtain the first product;
[0323] 1 mol of the first product and 1.5 mol of the anchoring capping agent Cl-C 4 H 8 -COOH was dissolved in 1000 ml of dichloromethane and halogenated at room temperature. After 6 hours of reaction, 500 ml of deionized water was added to quench the reaction. The reaction mixture was extracted three times with dichloromethane, the oil phase product was collected, and then dried with magnesium sulfate, the product was separated by rotary evaporation, and finally separated by chromatography to obtain polymer dispersant P-1.
[0324] The reaction process for preparing polymer dispersant P-1 is as follows:
[0325]
[0326] Among them, R 1 , R 2 , R 4 for
[0327] 2) Preparation of positive electrode slurry
[0328] The positive electrode active material carbon-coated lithium iron phosphate (LFP@C), conductive agent acetylene black (SP), binder polyvinylidene fluoride (PVDF), and dispersant (P-1) were added to N-methylpyrrolidone (NMP) and stirred to obtain a positive electrode slurry, wherein the weight ratio of LFP@C, SP, and PVDF was 97:2:1, the mass fraction of the dispersant was 1.5% of the total mass of the positive electrode active material, conductive agent, binder, and dispersant, and the theoretical solid content of the positive electrode slurry was 60%. After stirring, the slurry viscosity was tested and the viscosity was controlled to be less than 20000mPa·s. If the viscosity is high, add NMP in the minimum amount to make the slurry viscosity lower than 20000mPa·s.
[0329] 3) Preparation of positive electrode sheet
[0330] The positive electrode slurry is evenly coated on the two surfaces of the aluminum foil positive electrode current collector, and then dried to obtain a film layer; thereafter, it is cold pressed and cut to obtain a positive electrode sheet.
[0331] 4) Preparation of negative electrode sheet
[0332] The negative electrode active material artificial graphite, the conductive agent carbon black, the binder styrene-butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC-Na) are dissolved in the solvent deionized water in a weight ratio of 96:2:1:1, and mixed evenly to prepare a negative electrode slurry; the negative electrode slurry is evenly coated on the two surfaces of the negative electrode collector copper foil multiple times, and the negative electrode sheet is obtained after drying, cold pressing, and slitting.
[0333] 5) Isolation film
[0334] Polypropylene film is used as the isolation film.
[0335] 6) Preparation of electrolyte
[0336] In an argon atmosphere glove box (H 2 O<0.1ppm, O 2 <0.1ppm), organic solvents ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed evenly in a volume ratio of 3 / 7, and LiPF 6 The lithium salt is dissolved in an organic solvent to prepare a 12.5% solution to obtain an electrolyte.
[0337] 7) Preparation of secondary batteries
[0338] The positive electrode sheet, separator, and negative electrode sheet prepared in Example 1 are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare cell, and the bare cell is welded with a pole ear, and the bare cell is placed in an aluminum shell, and baked at 80°C to remove water, and then the electrolyte is injected and sealed to obtain an uncharged battery. The uncharged battery is then subjected to the processes of static, hot and cold pressing, formation, shaping, and capacity testing in sequence to obtain the lithium-ion battery product of Example 1.
[0339] Example 2-12
[0340] The preparation method of the battery of Example 2-12 is similar to that of the battery of Example 1, but the type of anchoring capping agent is adjusted, and then the structural formula of the polymer is adjusted. The specific adjustment parameters are shown in Table 1.
[0341] Table 1
[0342]
[0343]
[0344] Wherein X' in the polymer structures of Examples 1 to 12 comprises -C 12 H 25 , the L segment contains Where R 1 , R 2 , R 4 for
[0345] Examples 13-18
[0346] The preparation method of the battery of Examples 13-18 is similar to that of the battery of Example 1, but the types of diamine, dibasic acid and diol are adjusted, thereby adjusting the R 1 , R 2 , R 4 The structure of the specific adjustment parameters is shown in Table 2. The corresponding R 1 , R 2 , R 4 The groups are shown in Table 3.
[0347] Table 2
[0348] Serial number Dibasic Acid Diols Diamine Embodiment 13 <![CDATA[HOOC-(EO) 4 -COOH]]> <![CDATA[HO-(EO) 4 -(Monday) 2 -OH]]> <![CDATA[H 2 N-(EO) 4 -(PO)2 - NH 2 ]]> Embodiment 14 <![CDATA[HOOC-(CH 2 ) 6 -CooH]]> <![CDATA[HO-(EO) 4 -(Monday) 2 -OH]]> <![CDATA[H 2 N-(EO) 4 -(PO) 2 -NH 2 ]]> Embodiment 15 <![CDATA[HOOC-(EO) 4 -(BIT) 2 -COOH]]> <![CDATA[HO-(CH 2 ) 6 -OH]]> <![CDATA[H 2 N-(EO) 4 -(PO) 2 -NH 2 ]]> Example 16 <![CDATA[HOOC-(EO) 4 -(BIT) 2 -COOH]]> <![CDATA[HO-(EO) 4 -OH]]> <![CDATA[H 2 N-(EO) 4 -(PO) 2 -NH 2 ]]> Embodiment 17 <![CDATA[HOOC-(EO) 4 -(BIT) 2 -COOH]]> <![CDATA[HO-(EO) 4 -(Monday) 2 -OH]]> <![CDATA[H 2 N-(EO) 4 -NH 2 ]]> Embodiment 18 <![CDATA[HOOC-(EO) 4 -(BIT) 2 -COOH]]> <![CDATA[HO-(EO) 4 -(Monday) 2 -OH]]> <![CDATA[H 2 N-(CH 2 ) 6 -NH 2 ]]>
[0349] Table 3
[0350] Serial number <![CDATA[R 1 ]]> <![CDATA[R 2 ]]> <![CDATA[R 4 ]]> Embodiment 13 <![CDATA[-(EO) 4 -]]> <![CDATA[-(EO) 4 -(AFTER) 2 -]]> <![CDATA[-(EO) 4 -(AFTER) 2 -]]> Embodiment 14 <![CDATA[-(CH 2 ) 6 -]]> <![CDATA[-(EO) 4 -(AFTER) 2 -]]> <![CDATA[-(EO) 4 -(AFTER) 2 -]]> Embodiment 15 <![CDATA[-(EO) 4 -(AFTER) 2 -]]> <![CDATA[-(CH 2 ) 6 -]]> <![CDATA[-(EO) 4 -(AFTER) 2 -]]> Example 16 <![CDATA[-(EO) 4 -(AFTER) 2 -]]> <![CDATA[-(EO) 4 -]]> <![CDATA[-(EO) 4 -(AFTER) 2 -]]> Embodiment 17 <![CDATA[-(EO) 4 -(AFTER) 2 -]]> <![CDATA[-(EO) 4 -(AFTER) 2 -]]> <![CDATA[-(EO) 4 -]]> Embodiment 18 <![CDATA[-(EO) 4 -(AFTER) 2 -]]> <![CDATA[-(EO) 4 -(AFTER) 2 -]]> <![CDATA[-(CH 2 ) 6 -]]>
[0351] Examples 19-26
[0352] Compared with Example 1, the number of repeating units of the structural units represented by Formula II and Formula III is adjusted by adjusting the preparation parameters of the polymer. The specific preparation method is as follows:
[0353] Embodiment 19
[0354] Compared with Example 1, the molar ratio of the dibasic acid, the diol and the diamine was adjusted to 8.5:8:1.
[0355] Embodiment 20
[0356] Compared with Example 1, the molar ratio of the dibasic acid, the diol and the diamine was adjusted to 8.5:1:8.
[0357] Embodiment 21
[0358] Compared with Example 1, the process of preparing the intermediate polymer was adjusted, as follows:
[0359] Weigh the dibasic acid, diol and diamine in a molar ratio of 4:1:3.2, add them to a three-necked flask, and heat the water bath to 60°C to melt the above monomers. A large amount of nitrogen is introduced into the reaction system, and the system is heated to 140°C, and then heated to 195°C at a rate of 30°C / h. Then, 1% of the total mass of the above monomers is added with propylene glycol and 0.25% of the total mass of the above monomers as the catalyst n-butyl titanate, and stirred for 20 minutes. Then, a vacuum pump and a pressure regulating valve are used to gradually reduce the pressure of the reaction system to 60Pa. After reaching the maximum vacuum degree, the system is heated to 200°C. After reacting for 1.5 hours, the system is cooled down, and the material is discharged after the pressure inside and outside the reaction device is equalized to obtain an intermediate polymer with hydroxyl groups at both ends.
[0360] Embodiment 22
[0361] Compared with Example 1, the process of preparing the intermediate polymer was adjusted, as follows:
[0362] Weigh the dibasic acid, diol and diamine in a molar ratio of 4:3.2:1, add them to a three-necked flask, and heat the water bath to 60°C to melt the above monomers. A large amount of nitrogen is introduced into the reaction system, and the system is heated to 140°C, and then heated to 195°C at a rate of 30°C / h. Then add 1% of the total mass of the above monomers in propylene glycol and 0.25% of the total mass of the above monomers in the catalyst n-butyl titanate, and stir for 20 minutes. Then use a vacuum pump and a pressure regulating valve to gradually reduce the pressure of the reaction system to 60Pa. After reaching the maximum vacuum, the system is heated to 200°C. After reacting for 1.5 hours, the system is cooled, and the material is discharged after the pressure inside and outside the reaction device is equal to obtain an intermediate polymer with hydroxyl groups at both ends.
[0363] Embodiment 23
[0364] Compared with Example 1, the preparation method of the intermediate polymer was adjusted, as follows:
[0365] Weigh the dibasic acid, diol and diamine in a molar ratio of 2:1.2:1, add them to a three-necked flask, heat the water bath to 60°C to melt the above monomers, introduce a large amount of nitrogen into the reaction system, and heat the system to 70°C, and then heat it to 110°C at a rate of 10°C / h. Then add 1% of the total mass of the above monomers in propylene glycol and 0.25% of the total mass of the above monomers in the catalyst n-butyl titanate, and stir for 20 minutes. Then use a vacuum pump and a pressure regulating valve to gradually reduce the pressure of the reaction system to 60Pa, and after reaching the maximum vacuum degree, heat the system to 140°C. After reacting for 1 hour, cool the system, and discharge the material after the pressure inside and outside the reaction device is equal, to obtain an intermediate polymer with hydroxyl groups at both ends.
[0366] Embodiment 24
[0367] Compared with Example 1, the preparation method of the intermediate polymer was adjusted, as follows:
[0368] Weigh the dibasic acid, diol and diamine in a molar ratio of 2:1.2:1, add them to a three-necked flask, heat the water bath to 60°C to melt the above monomers, introduce a large amount of nitrogen into the reaction system, and heat the system to 70°C, and then heat it to 110°C at a rate of 10°C / h. Then add 1% of the total mass of the above monomers in propylene glycol and 0.25% of the total mass of the above monomers in the catalyst n-butyl titanate, and stir for 20 minutes. Then use a vacuum pump and a pressure regulating valve to gradually reduce the pressure of the reaction system to 60Pa, and after reaching the maximum vacuum degree, heat the system to 140°C. After reacting for 1.5 hours, cool the system, and discharge the material after the pressure inside and outside the reaction device is equal, to obtain an intermediate polymer with hydroxyl groups at both ends.
[0369] Embodiment 25
[0370] Compared with Example 1, the preparation method of the intermediate polymer was adjusted, as follows:
[0371] Weigh the dibasic acid, diol and diamine in a molar ratio of 2:1.2:1, add them to a three-necked flask, heat the water bath to 60°C to melt the above monomers, introduce a large amount of nitrogen into the reaction system, and heat the system to 70°C, and then heat it to 110°C at a rate of 10°C / h. Then add 1% of the total mass of the above monomers in propylene glycol and 0.25% of the total mass of the above monomers in the catalyst n-butyl titanate, and stir for 20 minutes. Then use a vacuum pump and a pressure regulating valve to gradually reduce the pressure of the reaction system to 60Pa, and after reaching the maximum vacuum degree, heat the system to 250°C. After reacting for 6 hours, cool the system, and discharge the material after the pressure inside and outside the reaction device is equal, to obtain an intermediate polymer with hydroxyl groups at both ends.
[0372] Embodiment 26
[0373] Compared with Example 1, the preparation method of the intermediate polymer was adjusted, as follows:
[0374] Weigh the dibasic acid, diol and diamine in a molar ratio of 2:1.2:1, add them to a three-necked flask, heat the water bath to 60°C to melt the above monomers, introduce a large amount of nitrogen into the reaction system, and heat the system to 70°C, and then heat it to 110°C at a rate of 10°C / h. Then add 1% of the total mass of the above monomers in propylene glycol and 0.25% of the total mass of the above monomers in the catalyst n-butyl titanate, and stir for 20 minutes. Then use a vacuum pump and a pressure regulating valve to gradually reduce the pressure of the reaction system to 60Pa, and after reaching the maximum vacuum, heat the system to 250°C. After reacting for 12 hours, cool the system, and discharge the material after the pressure inside and outside the reaction device is equal, to obtain an intermediate polymer with hydroxyl groups at both ends.
[0375] Examples 27-30
[0376] Compared with Example 1, the mass fraction of the polymer dispersant is adjusted, see the Example table for details.
[0377] Examples 31-34
[0378] Compared with Example 1, the graphitization degree of lithium iron phosphate is adjusted, see the example table for details.
[0379] Embodiment 35
[0380] Compared with Example 1, the positive electrode active material is adjusted to carbon-coated LiNi 0.6 Co 0.2 Mn 0.2 O 2 (NCM@C).
[0381] Embodiment 36
[0382] Compared with Example 1, the type of diamine was adjusted, and the structural formula of the diamine is shown below:
[0383]
[0384] Comparative Examples 1-4
[0385] Compared with Example 1, the dispersant is replaced with a polyvinyl pyrrolidone (PVP) dispersant, and the graphitization degree of the lithium iron phosphate is adjusted.
[0386] Comparative Example 5
[0387] Compared with Example 1, the dispersant is replaced with a polymer dispersant D-1, whose structural formula is C 12 H 25 -O-(EO) 80 -(PO) 40 -(CH 2 ) 4-COOH, the preparation process is as follows:
[0388] With 1 mol of C 12 H 25 -OH is an initiator, KOH with a mass percentage of 0.5% of the initiator is a catalyst, the system is evacuated and filled with nitrogen, the reaction device is then heated to 130°C and evacuated, 85 mol of ethylene oxide gas is then introduced, the pressure in the reaction device is maintained below 0.3 MPa, the reaction is carried out at this pressure and temperature for 1 hour, and the first product is obtained by cooling; then KOH with a mass percentage of 0.5% of the initiator is added, the system is evacuated and filled with nitrogen, the reaction device is then heated to 130°C and evacuated, 45 mol of propylene oxide gas is then introduced, the reaction is carried out for 1 hour, the product is obtained by cooling, and the product is further neutralized by acid washing, extracted three times with dichloromethane, dried, filtered and rotary evaporated to obtain an intermediate product.
[0389] 1 mol of the intermediate product and 1.5 mol of the anchoring capping agent Cl-C 4 H 8 -COOH was dissolved in 1000 ml of dichloromethane and subjected to halogenation reaction at room temperature. After 6 hours of reaction, 500 ml of deionized water was added to quench the reaction. The reaction mixture was extracted three times with dichloromethane, the oil phase product was collected, and then dried with magnesium sulfate, the product was separated by rotary evaporation, and finally separated by chromatography column to obtain polymer dispersant D-1.
[0390] Comparative Example 6
[0391] Compared with Example 1, the dispersant was replaced with polymer dispersant D-2, and the preparation process thereof was compared with Example 1, and the anchoring end-capping agent was adjusted to Cl-C 4 H 8 -CH 3 .
[0392] 2. Performance Test
[0393] 1. Characterization of polymers
[0394] 1) Weight average molecular weight
[0395] A Waters 2695 Isocratic HPLC gel chromatograph (differential refractive index detector 2141) was used. A polystyrene solution sample with a mass fraction of 3.0% was used as a reference, and a matching chromatographic column was selected (oily: Styragel HT5 DMF7.8*300mm+Styragel HT4). A 3.0% polymer solution was prepared with purified N-methylpyrrolidone (NMP) solvent, and the prepared solution was allowed to stand for one day for use. During the test, tetrahydrofuran was first drawn with a syringe and rinsed, and repeated several times. Then 5 ml of the experimental solution was drawn, the air in the syringe was expelled, and the needle tip was wiped dry. Finally, the sample solution was slowly injected into the injection port. Data was obtained after the indication stabilized.
[0396] 2) Glass transition temperature
[0397] The glass transition temperature was tested using a TA company's differential scanning calorimeter (Q1000). Take 6-9g of polymer sample, heat it from room temperature to 200°C at a heating rate of 10°C / min, and analyze the obtained differential scanning calorimetry curve to obtain the glass transition temperature of the polymer in °C.
[0398] 3) Melting point
[0399] Use a precision microscopic melting point tester (X-5 model) to test the melting point. Test under a standard atmospheric pressure, take 0.01 mg of uniformly ground sample and place it on a glass slide, cover it with another layer of glass slide and gently compact it, and place it in the center of the hot stage. Cover it with a heat insulation board and adjust the focus of the microscope until the sample can be clearly observed. Then adjust the temperature knob, quickly raise the temperature until the polymer melts slightly, and then slowly adjust the heating rate until the sample is completely melted. Record the full melting temperature as the melting point of the polymer in ℃.
[0400] 4) Hydrophile-Lipophile Balance (HLB)
[0401] The emulsification method is used for determination. The principle is that when the polymer is used to emulsify the oily medium, when the HLB value of the polymer is the same as the HLB value required by the oil phase medium, the generated emulsion has the best stability. The ideal HLB value can be obtained by mixing the standard sample with a known HLB value in proportion. The polymer is emulsified into the prepared oil phase and left to stand for 24 hours. The HLB value required by the oil phase in the sample with the best stability is the HLB value of the polymer.
[0402] 2. Positive electrode active material
[0403] 1) Graphitization degree
[0404] The graphitization degree was characterized by a French HORIBA Jobin Yvon high-resolution Raman spectrometer, model LabRAM HR Evlution, and the following Gaussian function was used for fitting after deducting the detection background. Raman spectrum test conditions: wavelength 532nm, scanning range 200-4000cm -1 , accumulate twice, measure 10 points for each sample, and take the average value for fitting:
[0405]
[0406] In the above formula, G is the degree of graphitization, Ai, Vi and wi are the peak intensity, peak position and peak width respectively.
[0407] 3. Cathode slurry
[0408] 1) Solid content
[0409] Take the copper foil and weigh it in the weight loss rate measuring instrument, record it as M0, and reset it to zero;
[0410] Take a small amount of the positive electrode slurry, apply it on the copper foil, and then put it into the moisture meter to weigh it, which is recorded as M1;
[0411] Close the device and start drying;
[0412] After completion, record the weighing data as M2, and calculate the solid content, which is (M2-M0) / (M1-M0).
[0413] 2) Slurry stability test
[0414] After re-stirring the slurry for 30 minutes, take a certain amount of slurry and pour it into the sample bottle of the stability instrument. After putting it into the sample bottle, close the test tower cover, open the test tower cover, and a scanning curve will begin to appear on the test interface, and the sample stability test will begin. The test will be completed after more than 72 hours of continuous testing.
[0415] 4. Positive electrode
[0416] 1) Brittleness test
[0417] Take a defect-free positive electrode sheet and cut it into samples with a length and width of 20cm*2.5cm in the longitudinal direction. The number of samples should be ≥8. After pre-folding it in half, place the film on the test platform and roll it once with a 2kg cylindrical roller. If it is light-transmitting, the number of times of brittle light transmission is 1. If it is not light-transmitting, repeat the reverse folding and rolling. Observe the crease against the light to see if it is light-transmitting or broken, record the actual number of folds, and take the average as the test result.
[0418] 2) Diaphragm resistance
[0419] Cut the dried positive electrode slurry (film layer) at the left, middle and right of the positive electrode sheet into small discs with a diameter of 3mm. Turn on the power of Yuanneng Technology's electrode sheet resistor meter, place the "probe" of the electrode sheet resistor meter in a suitable position, click the "start" button, and wait for the reading to stabilize before reading. Test two positions of each small disc, and finally calculate the average value of six measurements, which is the resistance of the electrode sheet film layer.
[0420] 5. Secondary battery
[0421] 1) First Coulombic efficiency
[0422] At 25°C, the batteries of the above embodiments and comparative examples were charged at a constant current of 0.1C to a voltage of 4.3V. The charging capacity at this time was recorded as the first-cycle charging capacity of the secondary battery. After that, they were allowed to stand for 5 minutes, and then discharged at a constant current of 0.1C to a voltage of 2.0V. The batteries were allowed to stand for 5 minutes. This was a charge and discharge cycle. The discharge capacity was recorded as the first-cycle discharge capacity of the secondary battery, which was the initial capacity of the secondary battery.
[0423] The first cycle coulombic efficiency of a secondary battery (%) = first cycle discharge capacity / first cycle charge capacity×100%.
[0424] 2) 45℃ cycle capacity retention rate
[0425] At 45°C, the batteries in the examples and comparative examples were charged to 3.65V at a constant current of 1 / 3C, then charged to a current of 0.05C at a constant voltage of 3.65V, left for 10 minutes, and then discharged to 2.5V at 1 / 3C. The obtained capacity was recorded as the initial capacity C0. Repeat the above steps for the same battery, and record the discharge capacity Cn of the battery after the nth cycle at the same time. The battery capacity retention rate after each cycle is:
[0426] Pn=C n / C 0 ×100%
[0427] During the test, the first cycle corresponds to n=1, the second cycle corresponds to n=2, ... the 100th cycle corresponds to n=100. The battery capacity retention rate data corresponding to Example 1 in Table 5 is the data measured after 300 cycles under the above test conditions, that is, the value of P300.
[0428] III. Analysis of test results of various embodiments and comparative examples
[0429] Table 4 Parameters and performance test results of the embodiment
[0430]
[0431]
[0432]
[0433] Table 5 Parameters and performance test results of the embodiment
[0434]
[0435]
[0436]
[0437] According to the above results, the polymers in Examples 1-36 include X'-LX, wherein X' includes -C 12 H 25 , X includes any one of a carboxyl group, an ester group, a sulfonic acid group, a sulfonate group, a phosphoric acid group, and a phosphoric acid ester group,
[0438] L comprises a structural unit represented by formula II and the structural unit shown in formula III
[0439]
[0440] Where R 1 With R 3 Same, R 1 Include
[0441]
[0442] R 2 Include R 3 Include
[0443] R 4 Include R 5 Contains hydrogen or methyl.
[0444] From the comparison of Examples 1-26, 31-34, and 36 with Comparative Examples 1-4, it can be seen that compared with the traditional PVP dispersant, the polymer dispersant of the present application has a wide range of versatility, can improve the dispersibility of the slurry with lithium iron phosphate of different graphitization degrees as the positive electrode active material, can effectively increase the solid content of the slurry, slow down the gelation of the slurry, reduce the membrane resistance of the pole piece, improve the flexibility of the pole piece, and improve the first coulomb efficiency and high temperature cycle performance of the battery. The polymer dispersant is universal for the positive electrode slurry of lithium iron phosphate with different graphitization degrees produced by different processes, which helps to reduce the preparation cost and improve the production efficiency.
[0445] From the comparison between Example 1 and Comparative Example 5, it can be seen that the ester group and amide group in the structural unit shown in Formula II and Formula III in the polymer dispersant of the present application can effectively increase the solid content of the slurry, slow down the gelation of the slurry, improve the flexibility of the pole piece, reduce the membrane resistance of the pole piece, and improve the first coulombic efficiency and high temperature cycle performance of the battery. From the comparison between Examples 1-12 and Comparative Example 6, it can be seen that the polymer dispersant of the present application containing the X group of carboxyl, ester, sulfonic acid, sulfonate, phosphoric acid or phosphoric acid ester can effectively increase the solid content of the slurry, slow down the gelation of the slurry, improve the flexibility of the pole piece, reduce the membrane resistance of the pole piece, and improve the first coulombic efficiency and high temperature cycle performance of the battery.
[0446] From the comparison between Examples 1, 9-10 and Example 5, it can be seen that compared with the 4 H 8 -COO-C 3 H 7 The X group, the polymer contains -C 4 H 8 -COOH, -C 4 H 8 -COO-C 3 H 6 -OH or -C 4 H 8 -COO-NH-C 3 H 6 The X group of -OH can further improve the dispersibility of the slurry, increase the solid content of the slurry, and improve the performance of the slurry. 4 H 8 -COO-C 3 H 7 , -C 4 H 8 -COO-C 3 H 6 -OH or -C 4 H 8 -COO-NH-C 3 H 6 -OH X group, the polymer dispersant contains -C 4 H 8 The X group of -COOH can further improve the dispersion effect of the slurry, increase the solid content of the slurry, slow down the gelation of the slurry, improve the flexibility of the electrode, and improve the performance of the slurry and the electrode. 4 H 8 -SO 3 -C 3 H 7 The X group, the polymeric dispersant comprises -C4 H 8 -SO 3 The X group of H can further improve the dispersion effect of the slurry, increase the solid content of the slurry, slow down the gelation of the slurry, improve the flexibility of the electrode, and improve the high temperature cycle performance of the battery.
[0447] Polymer dispersants include
[0448] The dispersibility of the slurry can be further improved, the solid content of the slurry can be increased, and the performance of the slurry can be improved.
[0449]
[0450] Polymer dispersants include The solid content of the slurry can be further increased, the gelation of the slurry can be slowed down, the flexibility of the pole piece can be improved, and the initial coulombic efficiency of the battery can be improved. Polymer dispersants include It can further slow down the gelation of the slurry, improve the flexibility of the pole piece, and improve the first coulombic efficiency and high temperature cycle performance of the battery. Polymer dispersants include The first coulombic efficiency and high temperature cycle performance of the battery can be improved, and the electrochemical performance of the battery can be improved. Polymer dispersants include The solid content of the slurry can be further increased, the flexibility of the electrode can be improved, and the initial coulombic efficiency of the battery can be improved.
[0451] From the comparison between Example 1 and Example 37, it can be seen that compared with R in the structural unit shown in Formula III 5 Contains methyl, R 5 The inclusion of hydrogen can further improve the dispersibility of the slurry, increase the solid content of the slurry, slow down the gelation of the slurry, improve the flexibility of the electrode, and improve the performance of the electrode.
[0452] From the comparison between Examples 1 and 13 and Example 14, the comparison between Examples 1 and 16 and Example 15, and the comparison between Examples 1 and 17 and Example 18, it can be seen that R 1 , R 2 , R 3 , R4 Include The solid content of the slurry can be increased, the flexibility of the electrode sheet can be increased, and the high temperature storage performance of the battery can be improved. 1 , R 2 , R 3 , R 4 Include The solid content of the slurry can be further increased, the gelation of the slurry can be slowed down, the flexibility of the electrode can be improved, and the high-temperature storage performance of the battery can be improved.
[0453] From Examples 1, 19-26, it can be seen that the ratio of the number of repetitions of the structural unit shown in Formula II to the number of repetitions of the structural unit shown in Formula III is 1:7-7:1, the slurry has a high solid content, the pole piece has excellent flexibility, and the battery has excellent first coulombic efficiency and high-temperature storage performance. From the comparison of Examples 1, 21-26 with Examples 19-20, it can be seen that the ratio of the number of repetitions of the structural unit shown in Formula II to the number of repetitions of the structural unit shown in Formula III is 1:3-3:1, which can improve the flexibility of the pole piece and improve the first coulombic efficiency and high-temperature storage performance of the battery.
[0454] From the comparison between Examples 1, 24-25 and Examples 23 and 26, it can be seen that the repetition number of the structural unit shown in Formula II is 8-50, and the repetition number of the structural unit shown in Formula III is 8-50, which can further increase the solid content of the slurry, slow down the gelation of the slurry, improve the flexibility of the electrode, and improve the performance of the slurry and the electrode.
[0455] The positive electrode slurry of Examples 1-36 comprises a positive electrode active material, a conductive agent, a binder and a dispersant, wherein the dispersant is a polymer of the present application, and the positive electrode active material comprises lithium iron phosphate without a carbon coating layer on the surface, lithium iron phosphate with a carbon coating layer on the surface, or lithium nickel cobalt manganese with a carbon coating layer on the surface.
[0456] From the comparison between Example 1 and Example 35, it can be seen that compared with lithium nickel cobalt manganese whose positive electrode active material is a lithium iron phosphate with a carbon coating layer on the surface, the polymer dispersant of the present application is more suitable for lithium iron phosphate with a carbon coating layer on the surface, and can further increase the solid content of the slurry of lithium iron phosphate with a carbon coating layer on the surface, slow down the gelation phenomenon of the slurry, improve the flexibility of the electrode, reduce the membrane resistance, and improve the first coulombic efficiency and high-temperature storage performance of the battery.
[0457] It can be seen from Examples 1, 32-34 that the polymer dispersant of the present application is universal and is suitable for a slurry system with lithium iron phosphate having a graphitization degree of 10%-30% as the positive electrode active material. It can be seen from the comparison between Examples 1, 32-34 and Example 31 that the use of lithium iron phosphate having a graphitization degree of 10%-30% can further reduce the membrane resistance of the electrode and improve the first coulombic efficiency of the battery.
[0458] As can be seen from Examples 1, 27-30, based on the total mass of solid matter in the positive electrode slurry, the mass fraction of the polymer dispersant is 0.01%-3%, the slurry has a high solid content, the pole piece has excellent flexibility, and the battery has excellent first coulomb efficiency and high temperature storage performance. As can be seen from the comparison between Examples 1, 28-29 and Examples 27 and 30, based on the total mass of solid matter in the positive electrode slurry, the mass fraction of the polymer dispersant is 0.03%-2%, which can further improve the flexibility of the pole piece and improve the performance of the pole piece.
[0459] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A polymer, characterized in that The polymer comprises a structure shown in Formula I, X′-LX Formula I wherein X comprises at least one of a carboxyl group, an ester group, a sulfonic acid group, a sulfonate group, a phosphoric acid group, and a phosphoric acid ester group; X' comprises a nonpolar group; L comprises structural units represented by formula II and formula III, Where R1 contains C 1-12 Alkylene, C 6-12 Aromatic group, At least one of, R2 comprises C 1-12 Alkylene, C 6-12 Aromatic group, At least one of, R3 comprises C 1-12 Alkylene, C 6-12 Aromatic group, At least one of R4 comprises C 1-12 Alkylene, C6- 12 Aromatic group, At least one of R5 comprises hydrogen or C 1-3 alkyl, Wherein EO represents -CH2-CH2-O-, PO represents -CH(CH3)-CH2-O-, m1, m2, m3, and m4 are each independently an integer between 1 and 10, and n1, n2, n3, and n4 are each independently an integer between 0 and 10.
2. The polymer according to claim 1, characterized in that The polymer comprises at least one of the structures shown in Formula I-1, Formula I-2, Formula I-3, and Formula I-4, wherein a1 and a2 are each independently an integer between 2 and 12, and R6 and R7 are each independently hydrogen, C 1-12 Alkyl, C 1-12 Alkyl alcohol, *-NH-R 11 -OH, at least one of R8, R9, R 10 Each independently contains hydrogen, C 1-12 Alkyl, C 1-12 Alkyl alcohol, *-NH-R 12 -OH, At least one of the following, where R 11 , R 12 Each independently contains C 1-12 Alkylene, R 13 Contains C 1-12 Alkyl or C 6-30 Aromatic group.
3. The polymer according to claim 1, characterized in that The polymer comprises at least one of the structures shown in Formula I-1, Formula I-2, and Formula I-4, wherein a1 and a2 are each independently an integer between 2 and 12, and R6 and R7 are each independently hydrogen, C 1-12 Alkyl alcohol, *-NH-R 11 -OH, at least one, R 10 Contains hydrogen, C 1-12 Alkyl alcohol, *-NH-R 12 -OH, At least one of the following, where R 11 , R 12 Each independently contains C 1-12 Alkylene, R 13 Contains C 1-12 Alkyl or C 6-30 Aromatic group.
4. The polymer according to claim 1, characterized in that R5 in the structural unit represented by formula III contains hydrogen.
5. The polymer according to any one of claims 1 to 4, characterized in that The R1 comprises The R2 comprises The R3 comprises The R4 comprises At least one of n1, n2, n3, and n4 is 0, and m1, m2, m3, and m4 are each independently an integer between 2 and 10.
6. The polymer according to any one of claims 1 to 4, characterized in that The R1 comprises The R2 comprises The R3 comprises The R4 comprises Wherein n1, n2, n3, n4, m1, m2, m3, and m4 are each independently an integer between 1 and 10.
7. The polymer according to any one of claims 1 to 4, characterized in that The ratio of the number of repetitions of the structural unit represented by formula II in L to the number of repetitions of the structural unit represented by formula III is 1:7-7:
1.
8. The polymer according to any one of claims 1 to 4, characterized in that The ratio of the number of repetitions of the structural unit represented by formula II in L to the number of repetitions of the structural unit represented by formula III is 1:3-3:
1.
9. The polymer according to any one of claims 1 to 4, characterized in that The number of repetitions of the structural unit represented by formula II in the L is 8-50, and the number of repetitions of the structural unit represented by formula III in the L is 8-50.
10. The polymer according to any one of claims 1 to 4, characterized in that The X' comprises C 3-30 Alkyl, C 6-30 At least one of the aromatic groups.
11. The polymer according to any one of claims 1 to 4, characterized in that The weight average molecular weight of the polymer is 3000 g / mol-55000 g / mol.
12. The polymer according to any one of claims 1 to 4, characterized in that The glass transition temperature of the polymer is 30°C-150°C.
13. The polymer according to any one of claims 1 to 4, characterized in that The melting point of the polymer at 1 standard atmosphere is 60°C-210°C.
14. The polymer according to any one of claims 1 to 4, characterized in that The hydrophilic-lipophilic balance value of the polymer is 6-16.
15. A method for preparing a polymer, characterized in that: The preparation method comprises the following steps: 1) Polycondensation reaction: polymerizing at least one dibasic acid, at least one diol and at least one diamine to prepare an intermediate polymer, wherein the intermediate polymer comprises a structure shown in Formula IV, Y'-LY Formula IV wherein Y' and Y each independently contain at least one of a carboxyl group, a hydroxyl group, and an amino group; 2) End group reaction: reacting the end groups of the intermediate polymer to obtain a polymer having a structure shown in formula I, X′-LX Formula I wherein X comprises at least one of a carboxyl group, an ester group, a sulfonic acid group, a sulfonate group, a phosphoric acid group, and a phosphoric acid ester group; X' comprises a nonpolar group; L comprises structural units represented by formula II and formula III, Where R1 contains C 1-12 Alkylene, C 6-12 Aromatic group, At least one of, R2 comprises C 1-12 Alkylene, C 6-12 Aromatic group, At least one of, R3 comprises C 1-12 Alkylene, C 6-12 Aromatic group, At least one of R4 comprises C 1-12 Alkylene, C 6-12 Aromatic group, At least one of R5 comprises hydrogen or C 1-3 alkyl, Wherein EO represents -CH2-CH2-O-, PO represents -CH(CH3)-CH2-O-, m1, m2, m3, and m4 are each independently an integer between 1 and 10, and n1, n2, n3, and n4 are each independently an integer between 0 and 10.
16. The preparation method according to claim 15, characterized in that: The preparation method specifically comprises: Stirring a catalyst, at least one dibasic acid, at least one diol and at least one diamine at 20° C.-250° C. for 1 h-20 h to obtain the intermediate polymer, wherein both ends of the intermediate polymer have the same end group; The terminal groups at both ends of the intermediate polymer are reacted respectively to obtain the polymer.
17. A dispersant, characterized in that: The dispersant comprises the polymer according to any one of claims 1 to 14 or the polymer prepared by the preparation method according to claim 15 or 16.
18. Use of the polymer according to any one of claims 1 to 14 in a secondary battery.
19. A positive electrode slurry, characterized in that: The invention comprises a positive electrode active material, a conductive agent, a binder and a dispersant, wherein the dispersant comprises the polymer according to any one of claims 1 to 14.
20. The positive electrode slurry according to claim 19, characterized in that: The positive electrode active material includes lithium iron phosphate having a carbon coating layer on the surface.
21. The positive electrode slurry according to claim 20, characterized in that: The graphitization degree of the lithium iron phosphate with a carbon coating layer on the surface is 10%-30%.
22. The positive electrode slurry according to claim 19, characterized in that: The mass fraction of the dispersant is 0.01%-3%, based on the total mass of the solid matter in the positive electrode slurry.
23. The positive electrode slurry according to claim 19, characterized in that: The mass fraction of the dispersant is 0.03%-2%, based on the total mass of the solid matter in the positive electrode slurry.
24. A positive electrode plate, characterized in that: It comprises a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer is prepared from the positive electrode slurry according to any one of claims 19 to 23.
25. A secondary battery, characterized in that: It comprises a separator, a negative electrode plate, an electrolyte and the positive electrode plate as claimed in claim 24.
26. An electrical device, characterized in that: Includes the secondary battery as claimed in claim 25.
Citation Information
Patent Citations
Dispersing and softening agent for positive electrode slurry of lithium ion battery and application of dispersing and softening agent
CN115863643A
Ester-terminated polyamide gels
CN1238678A
Liquid fat phase composition of gelatinized polyamide with ester terminal
CN1280817A
Polyether / polyester containing, dispersing resins
CN1820834A
Polyester, polyesteramide, and polyamide compositions
US20220325035A1
Cited By
Lithium ion battery dispersant, preparation method and application thereof
CN122685601A